1995
DOI: 10.1002/glia.440140108
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial constituents of corpora amylacea and autofluorescent astrocytic inclusions in senescent human brain

Abstract: Corpora amylacea (CA) are cytoplasmic inclusions that accumulate in human brain in the course of normal aging, and to an even greater extent, in Alzheimer's disease and other neurodegenerative conditions. In senescent and Alzheimer-diseased human brains, astrocytes in limbic and periventricular regions exhibit red autofluorescent inclusions, homologous to Gomori-positive astrocyte granules previously described in the brains of aging rodents and other vertebrates. We have shown that Gomori inclusions in situ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…In eukaryotes, Hsp27, Hsp25, and ␣B-crystallines are found in protein granules of neurodegenerative diseases and after heat shock (33)(34)(35). In Drosophila, heat-induced granules dissolve after stress (36).…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotes, Hsp27, Hsp25, and ␣B-crystallines are found in protein granules of neurodegenerative diseases and after heat shock (33)(34)(35). In Drosophila, heat-induced granules dissolve after stress (36).…”
Section: Discussionmentioning
confidence: 99%
“…In young adult rats, subcutaneous CSH injections (150-300 mg/kg twice weekly for 3 weeks) induced 2-3 fold increases in numbers of peroxidase-positive astrocyte granules in the hippocampus, basal ganglia and other brain regions [24]. As in the case of the CSH-treated cultures, peroxidase-positive glial granules in the intact rat and human brain invariably exhibit mitochondrial epitopes in immunohistochemical preparations [19,25,26]. Further studies indicated that intracellular oxidative stress was likely responsible for the transformation of normal astrocyte mitochondria to peroxidase-positive inclusions in vitro and in the intact aging brain [5,[27][28][29].…”
Section: Peroxidase-positive Astrocytes: a Senescent Glial Phenotypementioning
confidence: 99%
“…In this regard, mitochondria may be particularly prone to iron deposition because of their involvement in heme and iron-sulfur synthesis. 10,11 The localization of iron to mitochondria may be highly undesirable as it may enhance the rate of mitochondrial decay and oxidant formation.…”
Section: Introductionmentioning
confidence: 99%